Did I ever tell you how lucky you are? - Seuss, Dr. (New York : Random House, 1973)
Compared to the problems of some of the creatures the old man describes, the boy is really quite lucky.
Mode of access: Internet.
SPEC: In the Lee Walp Family Juvenile Book Collection, Gift of the Lee Walp Family.